Pengaruh Media Gambar Berbasis Digital Terhadap Kemampuan Menulis Karangan Sederhana Siswa Kelas III SD - Nuryuni, Siti; Hodsay, Zahruddin; Pratama, Aldora (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
At the elementary school level, especially in early grades, practicing simple writing can serve as a strong foundation for students' literacy development. To ensure that the writing learning process is effective and enjoyable, appropriate instructional strategies that match the developmental characteristics of children are required. One such strategy is the use of engaging and contextual learning media, such as digital image-based media. The purpose of this study is to determine the extent of the influence of using digital image-based media on the writing ability of third-grade elementary school students. This research is a quantitative study using a quasi-experimental method, with a one-group pretest-posttest design. The population consists of all third-grade students at SDN 90 Palembang, with a sample of 25 students from class III A. Data were collected using a writing skills assessment rubric. The data analysis technique used was the Mann-Whitney U test. Based on data analysis using SPSS 26, the results of the Mann-Whitney U test showed a significance value of 0.000, which is less than 0.05. This means that H₀ is rejected and Hₐ is accepted, indicating that there is a significant influence of using digital image-based media on the ability to write simple essays among third-grade students at SDN 90 Palembang.